Distribution and ecological risk assessment of heavy metals in the sediments of Changli ecological monitoring area, northwest of Bohai Bay, China. Issue 1 (31st December 2022) - Wang, Qianqian; Duan, Weiyan; Yao, Xiaomeng; Guo, Xiaonan; Liu, Dongyang; Gao, Weiming; Zhang, Jianda
ABSTRACT: The concentrations of six heavy metals were determined in the sediments of the Changli ecological monitoring area, northwest of the Bohai Bay. The spatial distribution of the metals was discussed, and the ecological risk was evaluated using the potential ecological risk index ( PERI ) and secondary phase enrichment factor ( KSPEF ). The content ranges of Cu, Pb, Cd, Cr, Ni, and Zn were 1.38–25.78, 11.13–21.96, 0.12–0.54, 15.44–120.60, 0.48–57.11, and 44.21–156.38 mg·kg −1, respectively. Based on the results of the geochemical speciation analysis, the residual phase was the main form for all five metals (Cu, Pb, Cd, Cr, and Zn). Compared to the assessment results of KSPEF, PERI is more suitable for the pollution evaluation of heavy metals. The results indicated that all the sediments pose a moderate to considerable level of risk, except site S14 (low risk), and Cd was found to be the main contributor of the ecological risk due to heavy metals.